The Principle of Language Politeness in the Discourse of Husband-Wife Dialogue at Toronge, Baranti District of Sidenreng Rappang Regency - Harmita Sari; Sukmawati Tono Palangngan; Samsinar Samsinar; Pancana Beta (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The purpose of this study was to determine the principle of language politeness in the discourse of husband-wife dialogue in the village community. The sources of data in this study were the husband and wife community of the Tonronge Village, Baranti District, Sidenreng Rappang Regency. This type of research used qualitative descriptive research to clearly describe the form of the principle of language politeness. Data collection techniques consisted of observation, recording, tapping techniques, and documentation. The results showed that the principle of language politeness in society in the discourse of husband-wife dialogue in the community reflects the implementation of the cultural values of "siri" as a central value. The use of special vocabulary, such as taalani (please get it), ta (yours), iye (yes), ki (you) shows politeness in language.